Manajemen Investasi Bank Syari’ah - M F Hidayatullah (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2014)
Financing activities which is one of the main tasks of Islamic banks, also became one of the sources of revenue for Islamic banks, namely when the business is financed successfully giving the profit sharing in accordance with the target. Instead, the bank will experience a loss when the Shari'ah is apparently stalled investment, as channeled to companies that are not growing, or even bankruptcy. In order to the investment made by Islamic banks can provide a profit as expected, it is necessary to do investment analysis and monitoring. This paper will review about the investment management for Islamic banks.